The Neuroplastic Adaptation Trident Model: A Suggested Novel Framework for ACL Rehabilitation - Timothy Machan; Kody Krupps (International Journal of Sports Physical Therapy)
Anterior Cruciate Ligament (ACL) injuries are common in athletic populations and there are many factors that contribute to a return to play decision. Human movement is diverse and variable, and it is important for patients recovering from an ACL injury to develop a variety of movement strategies for athletic performance. Variability of movement during sport may help to decrease injury risk by preparing the individual to handle many different situations and improve problem solving. ACL injuries result in neurophysiological dysfunction due to a disruption of the afferent information from the native mechanoreceptors in the ligament. Following injury, the brain enters a neuroplastic state and can adapt and change positively or negatively based on the rehabilitation or lack thereof. This commentary presents a novel framework for rehabilitation called the Neuroplastic Adaptation Trident Model that takes into account respected methods for attempting to achieve positive neuroplastic changes. This structured framework provides clinicians with reproducible methods to employ as part of the rehabilitation process to maximize motor control and motor learning. Suggested dosage and implementation are proposed to lead to a consistent and gradually progressive challenge throughout the entire rehabilitation process that takes advantage of the time from surgery until return to play. The purpose of this clinical commentary is to describe the Neuroplastic Adaptation Trident model and provide examples for clinical implementation. This method should be studied further to determine true effectiveness; currently, it is presented as a theoretical model based on best current evidence regarding ACL injury and rehabilitation of neurophysiologic dysfunction.